Scale-dependent landscape variables and linear infrastructures influence smooth newt (Lissotriton vulgaris) abundance in wetlands of a heavily urbanized lake - Boglárka Mészáros; József Bürgés; Mónika Tamás; Blanka Gál; Judit Vörös; Andrew J. Hamer; Dénes Schmera (Scientific Reports)
Abstract The degradation of freshwater ecosystems due to land use changes is one of the major driver of global biodiversity loss and amphibian declines with these impacts varying across different spatial scales. Our study aimed to assess how natural and human-modified land affects smooth newt (Lissotriton vulgaris) abundance in the surrounding waterbodies of Lake Balaton, a highly urbanized area. We conducted aquatic trap surveys at 32 wetland sites during the breeding season and quantified land cover within 250, 500, and 1000-m radius buffer zones. We hypothesized that urban land use, cropland, and proximity to roads and railways would negatively correlate with newt abundance, while wetlands areas (marshes, swamps, periodically flooded grasslands) and natural terrestrial habitats (grasslands, forests and woodlands) would positively correlate, with effects varying across spatial scales. N-mixture models were used to analyse survey data, estimating abundance and examining relationships with covariates. Results revealed that wetland cover within a 500-m buffer zone increased newt abundance, probably due to supporting metapopulation connectivity. In contrast, cropland cover within 250 m and proximity to roads and railways negatively affected newt abundance. Conservation efforts should prioritize providing smooth newts with adequate breeding habitats and reducing disturbances from croplands, roads, and railways.